Development of a new N-terminomic method to study the pathodegradome of the Staphylococcus aureus V8 protease in human neutrophils - Emilee M. Mustor; Andrew M. Frey; Mary-Elizabeth Jobson; Dale Chaput; Lindsey Neil Shaw (mSystems, 2025)
ABSTRACT Staphylococcus aureus is a notorious human pathogen that relies on an array of virulence factors to engender infection and evade the host-immune system. Among these are the secreted proteases, which promote pathogenesis by degrading host proteins and modulating host defenses. Human neutrophils play a pivotal role in these defenses, acting as the first responders against invading bacteria. While many S. aureus effectors of virulence have been shown to target leukocytes, there is limited knowledge on how the extracellular proteases modulate neutrophil fate. Typically, protease substrates have been identified in isolated settings using one-at-a-time approaches, with neutrophil targets few and far between. Herein, we have developed a novel N-terminomic methodology termed TAGS-CR that can facilitate global substrate characterization in a streamlined manner. We thus present the application of TAGS-CR to unraveling the human neutrophil pathodegradome of the S. aureus V8 protease. In so doing, we captured ~350 V8 targets, revealing critical insight into how this virulence factor can modulate neutrophil functionality on various levels relevant to S. aureus disease progression. We recorded the cleavage of proteins necessary for neutrophil adhesion and migration, a fundamental process necessary for pathogen clearance. Furthermore, we highlight the V8 cleavage of proteins involved in important neutrophil defense tactics, such as degranulation and reactive oxygen species production. This protease may also facilitate bacterial dissemination via the intentional activation of neutrophil apoptosis. Collectively, this work deepens our understanding of host-pathogen interaction and begins to unravel how S. aureus proteases can induce immune dysregulation through the targeting of leukocytes.IMPORTANCEDuring infection, Staphylococcus aureus must engage and evade the host immune system in order to successfully cause disease. As neutrophils represent the frontline of defense against invading S. aureus cells, it becomes increasingly important to decode how this bacterium subverts their host-defense tactics. While the contributing role to neutrophil engagement for many S. aureus virulence factors has been elucidated, the effects of their proteases remain largely unclear. Here, we present a novel method for global protease substrate identification, TAGS-CR, and use it to identify S. aureus V8 protease targets in human neutrophils. These include factors that not only govern general neutrophil function but moreover, their defense mechanisms, such as migration, degranulation, oxidative defense, phagocytosis, and apoptosis.